OBTENÇÃO, CARACTERIZAÇÃO E AVALIAÇÃO DAS ATIVIDADES ANTIOXIDANTE E ANTITUMORAL IN VITRO DE NANOPARTÍCULAS DE ALBUMINA CONTENDO RESVERATROL - FONSECA, DYENEFER PEREIRA (2016)
Resveratrol (3,5,4'-trihidroxiistilbeno) (RVT) is a phenolic phytoalexin produced by plants to protect them from the exogenous attack. Which present numerous pharmacologic properties, mostly as an excellent antioxidant, as well as acting directly in the carcinogenic process in their three stages: initiation, promotion and progression. Although its properties are compromised because of the low absorption and high metabolism, resulting in low availability and difficult biological application. The present study aimed the development of albumin (BSA) nanoparticles containing resveratrol (NP-RVT) in order to overcome the difficulties biopharmaceutical presented by the free RVT. The NP-RVT were obtained through the coacervation and the best results were when there was a insertion of the incubation time (1 h) in the technical. The developed NP-RVT presented average diameter of 175 ± 6 nm, polydispersity 0.130 ± 0.01, zeta potential of -37.4 ± 1.3 mV and encapsulation efficiency approaching 60%. Morphological analysis revealed that NP-RVT feature is spherical and smooth. In vitro, during 144 h there was a release of 26% of the RVT in PBS buffer (10 mM, pH: 7.4 with Tween 80, 1%) from the nanoparticles. The kinetic model that corresponds the release which is the second order for Fickian mechanism, with a quick initial release (brust effect) followed by a slower release being regulated by diffusion of RVT by the chain polymer. The physico-chemical analysis (x-ray, infrared spectroscopy and differential scanning calorimetry and fluorescence spectroscopy) showed that nanoencapsulation process resulted in an amorphous system with interactions between RVT and the BSA. With the stability study it was observed that both storage conditions - room temperature and refrigeration (2-8 ° C) - the RVT-NP were stable the period of three months. The applicabilities of NP-RVT was analyzed by studying the antioxidant potential of the system itself, containing RVT front ability of the radical sequestering (2,2'-azinobis (3-etilbenzotiazolinona sulfonic acid-6)) (ABTS • +) and inhibition of hypochlorous acid (HOCl) and cytotoxic evaluation in cell B16F10. The results showing that both tests NP-RVT were dose-dependent inhibition with 50% and 70% respectively in concentration of 5.0 mg / mL in time of 72 hours. In the assessment of cytotoxicity in B16F10 cell, after 96 h of the incubation NP-RVT inhibited 25% cell viability, possibly due to slow release RVT. With the test conducted it was concluded that the nanostructured system containing RVT was successfully obtained, which has a potential for application in treatments antioxidant and against tumor.